A catalog of the Bibionidae (Diptera: Bibionomorpha) of Chile - Fitzgerald, Scott J.; González, Christian R; Elgueta, Mario (Zootaxa, 2020)
A catalog of the Bibionidae of Chile is provided. We present all valid names and synonyms for the 33 species and 2 genera known from the country, including information about name, author, year of publication, page number, type species, type locality and references. The geographical distribution of the species known from Chile was compiled from bibliographic data and revised collections. Epiplecia Giard, Heteroplecia Hardy, and Pleciodes Hardy are proposed as junior synonyms of Plecia Wiedeman.